Current Status and Future Perspectives of the LUCIFER Experiment. (10th November 2013) - Beeman, J. W.; Bellini, F.; Benetti, P.; Cardani, L.; Casali, N.; Chiesa, D.; Clemenza, M.; Dafinei, I.; Di Domizio, S.; Ferroni, F.; Giachero, A.; Gironi, L.; et al.
Abstract : In the field of fundamental particle physics, the neutrino has become more and more important in the last few years, since the discovery of its mass. In particular, the ultimate nature of the neutrino (if it is a Dirac or a Majorana particle) plays a crucial role not only in neutrino physics, but also in the overall framework of fundamental particle interactions and in cosmology. The only way to disentangle its ultimate nature is to search for the neutrinoless double beta decay. The idea of LUCIFER is to combine the bolometric technique proposed for the CUORE experiment with the bolometric light detection technique used in cryogenic dark matter experiments. The bolometric technique allows an extremely good energy resolution while its combination with the scintillation detection offers an ultimate tool for background rejection. The goal of LUCIFER is not only to build a background-free small-scale experiment but also to directly prove the potentiality of this technique. Preliminary tests on several detectors containing different interesting DBD emitters have clearly demonstrated the excellent background rejection capabilities that arise from the simultaneous, independent, double readout of heat and scintillation light.